Microstructure of Foreign Exchange Markets - Martin D.D. Evans; Dagfinn Rime (Norges Bank, 2019)
This article presents an overview of research on the Microstructure of Foreign Exchange Markets. We begin by summarizing the institutional features of FX trading and describe how they have evolved since the 1980s. We then explain how these features are represented in microstructure models of FX trading. Next, we describe the links between microstructure and traditional macro exchange-rate models and summarize how these links have been explored in recent empirical research. Finally, we provide a microstructure perspective on two recent areas of interest in exchange-rate economics: the behavior of returns on currency portfolios, and questions of competition and regulation.
hdl:11250/2594139
Keywords: F3; F4; G1; 330; exchange-rate dynamics; microstructure; order flows; liquidity; electronic trading